Within- and between-session changes of in-session reflective functioning of mothers in dyadic parent-infant psychotherapy - Georg, Anna; Kasper, Lea A.; Neubauer, Andreas B.; Selic, Maximilian; Taubner, Svenja (Psychotherapy research, 2024)
This study investigated if in-session reflective functioning (RF) of mothers improved between and within sessions of brief dyadic focused parent-infant psychotherapy (fPIP) for the treatment of regulatory disorders in infants. In-session RF was coded for 44 therapy sessions from N = 11 mothers randomly selected from a RCT on the efficacy of fPIP as part of secondary analyses. A new rating system distinguished self-focused and child-focused in-session RF. Cumulative ordinal regression models were applied to analyze the dynamics of in-session RF within and across sessions, controlling for word count of each statement. While in-session RF improved significantly within sessions, between-session RF improved significantly only in the second session compared to the first with a significant decrease observed in the last session. Child-focused in-session RF was significantly lower than self-focused in-session RF at the beginning of the sessions but improved significantly stronger than self-focused in-session RF during sessions. In-session RF (particularly in child-focused statements) can be regarded as a dynamic change process relevant within each session of dyadic fPIP. Improvements made on a session-by-session basis may not be maintained until the next session. Implications for practitioners and in-session RF research are discussed.